Women at the center : Grameen Bank borrowers after one decade - Todd, Helen, 1943- (Dhaka, Bangladesh : University Press, 1996)
For two decades, the Grameen Bank of Bangladesh has successfully administered a unique program that lends small sums to poor women for income generation. This is the first empirical study to examine the long-term influence of these loans on the borrowers, and it demonstrates that credit alone can fundamentally change the lives of poor women - even in the absence of other aid programs and in an environment distinctly hostile to women's autonomy.
Helen Todd spent a year in two villages in Bangladesh following the lives of women who have been borrowing from the Grameen Bank for a decade. She focuses on the day-to-day processes of how they generate money from their tiny loans, what they do with the resulting income, and how much control they retain over it.
. In stark contrast with nonmembers, most Grameen women emerge from this study as strong individuals, successfully battling for positions of power in their families and for respect in their villages. Moreover, the Grameen women's gains have been sustainable, since most of them have invested in access to land. Through the vivid stories of individual women, Todd paints a picture of women empowering themselves with the crucial ingredient of continued access to credit over the course of a decade.
1. The Bank in the Village -- 2. What Credit Can Do: Women's Contribution -- 3. Wives and Partners -- 4. Taka Talks: Centrality in the Household -- 5. Strategies for Survival -- 6. Still Poor: Disaster and Dependency -- 7. Women on Their Own -- 8. Group and Center: Solidarity and Self-Interest -- 9. Centered on the Children -- Appendix 1: Methodology -- Appendix 2: Children's Growth -- Appendix 3: The Sixteen Decisions.
Includes bibliographical references (pages [245]-248) and index.
BIED
Keywords: Grameen Bank; Bank loans -- Bangladesh; Rural women -- Bangladesh; Poor women -- Bangladesh